Burden, clinical outcomes, and characteristics of tuberculosis in migrant populations in the middle East and North African region: A systematic review and meta-analyses - Taha Maatoug; Farah Seedat; Eman Elafef; Anissa Ouahchi; Ali Mtiraoui; Stella Evangelidou; Wejdene Mansour; Ana Requena-Méndez; Dominik Zenner (Travel Medicine and Infectious Disease)
Introduction: Migrants in the Middle East and North Africa (MENA) region face an increased tuberculosis (TB) risk due to socioeconomic and structural barriers. This systematic review synthesises evidence on TB burden, clinical outcomes, and epidemiological characteristics among migrants in MENA. Methods: We searched six electronic databases and grey literature sources for studies published between 2000 and September 2024 in any language. Eligible studies reported primary data on TB prevalence, incidence, treatment outcomes, and clinical or epidemiological features in migrants. Pooled estimates were calculated using DerSimonian & Laird's random-effects model where applicable or narratively synthesised. Results: Of the 779 records identified, we included 57 studies, comprising 95,190 TB cases and 3,532,359 migrants across 12 MENA countries. TB incidence was consistently higher in migrants than non-migrants (26.7–69.8/100,000 vs. 11.5–16.8/100,000). Migrants had lower TB-related mortality (pooled OR 0.8, 95 % CI 0.7–0.9; I2 = 2.9 %), however, treatment success rates were consistently below the WHO-recommended 90 % threshold. Migrant TB patients were younger (mean age difference: 12.8 years; 95 % CI 8.8–16.0; I2 = 86.5 %) and predominantly male (sex ratio: 1:5). Drug-resistant TB was more common among migrants, though this was not always statistically significant (multi-drug-resistant TB: pooled OR 1.2; 95 % CI 0.9–1.6; I2 = 40.2 %), while extrapulmonary TB was more prevalent among non-migrants (33.4–83.4 % vs. 16.6–72.9 %). Conclusion: Migrants in MENA region experience disproportionate TB burden and poorer treatment outcomes, underscoring the need for targeted interventions. Enhanced data, especially from North Africa, is essential to support regional TB elimination aligned with World Health Organization and Sustainable Development Goals.